2020
DOI: 10.16970/entoted.663690
|View full text |Cite
|
Sign up to set email alerts
|

Fungal pathogens of Amphimallon solstitiale Linnaeus, 1758 (Coleoptera: Scarabaeidae)

Abstract: European June beetle, Amphimallon solstitiale Linnaeus, 1758 (Coleoptera: Scarabaeidae) is one of the most important soilborne pests in many parts of Turkey and the world. Entomopathogenic fungi are important microbial control agents that can be used to control soilborne pests, and it is desirable to obtain them from local insect populations. The study was conducted at Karadeniz Technical University, Faculty of Science, Microbiology Laboratory in 2017. In this study, fungal pathogens of A. solstitiale were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The white conidia were initially observed on the insect cadaver 6 days after treatment in the moist chamber, then green conidia were observed 10 days after treatment Eski et al Egyptian Journal of Biological Pest Control (2022) 32:140 bassiana (SUA a38) isolate was less virulent and LC 50 value was 8.46 × 10 6 conidia/ml. Generally, isolates obtained from naturally infected insects are more virulent than those isolated from different habitats (Biryol et al 2020). As in this study, EPF isolated from a particular host or soil have shown to be virulent to other hosts.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The white conidia were initially observed on the insect cadaver 6 days after treatment in the moist chamber, then green conidia were observed 10 days after treatment Eski et al Egyptian Journal of Biological Pest Control (2022) 32:140 bassiana (SUA a38) isolate was less virulent and LC 50 value was 8.46 × 10 6 conidia/ml. Generally, isolates obtained from naturally infected insects are more virulent than those isolated from different habitats (Biryol et al 2020). As in this study, EPF isolated from a particular host or soil have shown to be virulent to other hosts.…”
Section: Discussionsupporting
confidence: 58%
“…Biryol et al (2020) As18A. solstitialeBiryol et al (2020) Metarhizium brunneum Gg12 Gryllotalpa grylotalpa (Orthoptera: Gryllotalpidae)Eski et al Egyptian Journal of Biological Pest Control (2022) 32:140 …”
mentioning
confidence: 99%
“…In the current study, we examined the effectiveness of four tea extracts as UV protectants using B. bassiana Pa4 and M. flavoviride As-2 isolates and their mortality on G. mellonella larvae. These isolates have demonstrated significant potential in previous studies focusing on biological control (Biryol et al, 2020(Biryol et al, , 2021.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, B. bassiana (Pa4) and M. flavoviride (As-2) were isolated from Pristiphora abietina (Christ, 1791) (Hymenoptera: Tenthredinidae) and Amphimallon solstitialis (Linnaeus, 1758) (Coleoptera: Scarabaeidae) in Türkiye, respectively. These fungi exhibited significant insecticidal activity on insect pests (P. abietina and A. solstitialis) (Biryol et al, 2020(Biryol et al, , 2021.…”
Section: Fungal Isolates and Conidia Productionmentioning
confidence: 99%
“…Control larvae were treated with 0.01% aqueous Tween 80. Assessments were conducted at 28 ± 2 °C and 16:8-hour light:dark photoperiod for 15 days (Biryol et al 2020). Dead insects were removed and placed in Petri dishes with moist filter paper to allow mycosis to occur.…”
Section: Screening Testsmentioning
confidence: 99%